Electrolytes for high voltage cathode materials and other applications

By using the electrolytes based on ion -based lyric compounds in lithium ion batteries, the problem of insufficient electrochemical stability under high oxidation potential has been solved, and higher safety and cycle performance are achieved.

CN113994517BActive Publication Date: 2025-01-28FACTORIAL INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202080038163.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-16
Filing Date
2020-07-13
Publication Date
2025-01-28
Estimated Expiration
2040-07-13

AI Technical Summary

Technical Problem

Existing lithium-ion batteries lack electrochemical stability at high oxidation potentials, and pose safety risks, such as the risk of flammability, combustion or explosion.

Method used

The electrolyte based on ion -based lyric compounds contains lithium salt, ion ionization compounds and polymers, and improves the stability and safety of electrolytes through cross -linking reactions.

Benefits of technology

The electrolytes that have electrochemical stability and safety under high oxidation potential, suitable for high -voltage lithium batteries and other electrochemical devices, which improves the safety and circulation performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113994517B_ABST
    Figure CN113994517B_ABST
Patent Text Reader

Abstract

The present invention generally relates to electrolytes for various electrochemical devices. In some cases, it is relatively safe to use the electrolyte; for example, the electrolyte can withstand overheating, fire, combustion, explosion, etc. In some embodiments, such electrolytes can be used for certain types of high-voltage cathode materials. In some cases, the electrolyte can include ion dissociation compounds that can dissociate tight ion pairs. Non-limiting examples of ion dissociation compounds include trialkyl phosphates or sulfones, etc. Other aspects of the present invention generally relate to devices including such electrolytes, methods for making or using such electrolytes, or kits including such electrolytes, etc.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to US non-provisional application serial number 16 / 512,495 filed on July 16, 2019. The entirety of the above patent application is hereby incorporated by reference herein and becomes a part of this specification. Technical Field

[0003] The present invention generally relates to electrolytes for use in various electrochemical devices. Background Art

[0004] As the energy density of lithium-ion batteries (LIBs) increases and their scale expands, high-voltage cathode materials have been widely developed, but are limited by the lack of suitable electrolytes with suitable electrochemical stability at high oxidation potentials. In addition, safety issues in lithium batteries may arise, for example, the use of mixed flammable solvents such as carbonates / ethers as solvent systems may lead to serious accidents caused by fire, combustion or even explosion when overcharged, short-circuited, overheated, etc. Therefore, there is still a need for suitable electrolytes that are safe and electrochemically stable at high oxidation potentials, for example, suitable for high-voltage lithium batteries and other uses. Summary of the invention

[0005] The present invention generally relates to electrolytes for various electrochemical devices. Examples of suitable electrochemical devices are, for example, batteries, capacitors, sensors, relays, electrochromic elements, photoelectric conversion elements, etc. In some cases, the use of electrolytes is relatively safe; for example, the electrolyte can withstand overheating, fire, combustion, explosion, etc. In some embodiments, such electrolytes can be used for certain types of high-voltage cathode materials. Non-limiting examples of such high-voltage cathode materials include LiNi 0.5 Mn 1.5 O4 (LNMO), LiCoPO4 (LCP), layered Li–Ni–Co–Mn oxide (NCM), layered Li–Ni–Co–Al oxide (NCA), etc. In some cases, the subject matter of the present invention relates to related products, alternative solutions to a particular problem, and / or multiple different uses of one or more systems and / or articles.

[0006] In one aspect, the present disclosure generally relates to various electrolytes based on ion dissociation compounds. As discussed herein, ion dissociation compounds can include any organic compound that can dissociate tight ion pairs. In some embodiments, ion dissociation compounds can also be chemically coordinated with ions dissociated from tight ion pairs. In some embodiments, ion dissociation compounds can be flame retardants. Non-limiting examples of ion dissociation compounds include trialkyl phosphates, sulfones or analogs of sulfones, etc. Other examples are also discussed below. In one embodiment, the present invention generally relates to electrolytes. In one group of embodiments, the electrolyte comprises a lithium salt, an ion dissociation compound, and a polymer. In some cases, the polymer comprises a cross-linked reaction product, which comprises a polymer selected from the group consisting of:

[0007]

[0008] wherein R1 comprises a structure selected from the group consisting of:

[0009]

[0010] wherein n is an integer between 1 and 10,000; wherein m is an integer between 1 and 5,000; wherein R2, R3, R4, R5 and R6 are each independently selected from the group consisting of:

[0011]

[0012] and where * indicates a connection point.

[0013] In another aspect, the present invention generally relates to a method for manufacturing a device. In one set of embodiments, the method includes mixing a liquid electrolyte and a polymer precursor into a cell, the liquid electrolyte comprising a lithium salt and an ion dissociation compound; and solidifying the liquid electrolyte in the cell to form a solid electrolyte. In some cases, the polymer precursor comprises a structure selected from the group consisting of:

[0014]

[0015] wherein R1 comprises a structure selected from the group consisting of:

[0016]

[0017] wherein n is an integer between 1 and 10,000; wherein m is an integer between 1 and 5,000; wherein R2, R3, R4, R5 and R6 are each independently selected from the group consisting of:

[0018]

[0019] and where * indicates a connection point.

[0020] Some embodiments are generally directed to various high oxidation potential electrolytes including a polymer comprising a cross-linked reaction product comprising a polymer selected from the group consisting of:

[0021]

[0022] wherein R1 comprises a structure selected from the group consisting of:

[0023]

[0024] wherein n is an integer between 1 and 10,000; wherein m is an integer between 1 and 5,000; wherein R2, R3, R4, R5 and R6 are each independently selected from the group consisting of:

[0025]

[0026] and where * indicates a connection point.

[0027] In one aspect, the present disclosure includes methods for preparing one or more embodiments described herein, such as electrolytes based on ion dissociative compounds. In another aspect, the present disclosure includes methods for making solid electrochemical devices.

[0028] In some cases, the electrolyte can be a high oxidation potential electrolyte.For example, in one set of embodiments, the method includes mixing a polymer with a solvent to form a slurry, removing the solvent, and curing the slurry to form a solid electrolyte.

[0029] In yet another aspect, the invention includes methods for preparing one or more embodiments described herein, such as electrolytes for various electrochemical devices. In yet another aspect, the invention includes methods for using one or more embodiments described herein, such as, for example, electrolytes for various electrochemical devices based on ion dissociation compounds.

[0030] Other advantages and novel features of the present invention will become apparent from the following detailed description of various non-limiting embodiments of the invention when considered in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Non-limiting embodiments of the present invention will be described by way of example with reference to the accompanying drawings, which are schematic and are not intended to be drawn to scale. In the drawings, each identical or nearly identical component shown is generally represented by the same number. For the purpose of clarity, not every component is labeled in each of the drawings, nor is every component of each embodiment of the present invention shown, wherein the description is not necessary for a person of ordinary skill in the art to understand the present invention. In the drawings:

[0032] Figure 1 showing a safety performance curve of an electrolyte according to certain embodiments of the present disclosure;

[0033] Figure 2 shows a cycle performance curve of an electrolyte according to some embodiments of the present disclosure;

[0034] Figure 3 showing an electrochemical stability curve of an electrolyte according to certain embodiments of the present disclosure; and

[0035] Figure 4 Cycling performance curves of electrolytes according to other embodiments of the present disclosure are shown. DETAILED DESCRIPTION

[0036] The present invention generally relates to electrolytes for various electrochemical devices. In some cases, it is relatively safe to use the electrolyte; for example, the electrolyte can withstand overheating, fire, combustion, explosion, etc. In some embodiments, such electrolytes can be used for certain types of high-voltage cathode materials. In some cases, the electrolyte can include ion dissociation compounds that can dissociate tight ion pairs. Non-limiting examples of ion dissociation compounds include trialkyl phosphates or sulfones, etc. Other aspects of the present invention generally relate to devices including such electrolytes, methods for preparing or using such electrolytes, or kits including such electrolytes, etc.

[0037] In one aspect, the present invention generally relates to electrolyte materials comprising electrolyte salts such as lithium salts or sodium salts, ion dissociation compounds and polymers. In some embodiments, these are generally related to various high oxidation potential electrolytes suitable for various electrochemical devices. In some cases, such electrolytes can show higher ionic conductivity. For example, ions such as lithium ions can conduct electricity faster and / or more efficiently in the electrolyte. This can be useful, for example, for faster charging / discharging of electrochemical devices.

[0038] Certain embodiments include ionic dissociation compounds. The ionic dissociation compound can be an organic compound. In some embodiments, the ionic dissociation compound can dissociate ion pairs present in solution (e.g., lithium ions from lithium NMC compounds), and in some cases, form chemical complexes with ions from the ion pairs (e.g., such as with lithium ions). Without wishing to be bound by any theory, it is believed that the complex is formed due to coordination chemistry; for example, the P=O group and the S=O group in a trialkyl phosphate or sulfone can coordinate with the Li cation to form a chemical complex, respectively. Non-limiting examples of ionic dissociation compounds include flame retardants, phosphates including organic phosphates, sulfones, or polar aprotic solvents, and the like. These ionic dissociation compounds and their reactions are discussed in more detail below.

[0039] In some embodiments, the polymer may be formed from a polymerization reaction including one or more of the following monomers:

[0040]

[0041] Wherein R1 can be one of the following groups:

[0042]

[0043] wherein n is an integer between 1 and 10,000, m is an integer between 1 and 5,000, and R2 to R6 can each independently be one of the following structures:

[0044]

[0045] In some cases, for example, in addition to these, other monomers may also be polymerized into polymers. In addition, in some cases, the introduction of urea functional groups or carbamate functional groups using UV cross-linking can be used to improve mechanical properties and / or electrochemical performance. Other examples of polymers include, but are not limited to, those described in U.S. Patent Application Serial No. 16 / 240,502, filed on January 4, 2019, entitled “Polymer Solid Electrolytes”, which is incorporated herein by reference in its entirety.

[0046] In certain embodiments, the electrode material can be surrounded by an electrolyte, such as one filled in a porous space within the electrode. For example, one aspect generally relates to an electrochemical device comprising an electrode comprising particles. Some or all particles can be surrounded by electrolytes such as solid electrolytes. In some cases, at least some holes or gaps between particles can be filled with electrolytes. Since particles can be surrounded by electrolytes so that at least some holes or gaps are filled with electrolytes, the contact between particles and the electrolyte can be very close. This can make the internal resistance of the electrochemical device lower, which can make the electrochemical device show a higher capacity. Examples of such electrodes can be found, for example, in U.S. patent application serial number 16 / 512,502, entitled "Electrodes for Lithium-Ion Batteries and Other Applications", which is incorporated herein by reference in its entirety.

[0047] In some cases, such electrolyte materials can be used in electrochemical devices such as batteries, capacitors, sensors, relays, electrochromic elements, photoelectric conversion elements, etc. For example, in certain embodiments, electrolyte materials such as those described herein can be used to make safer, longer-lasting lithium batteries.

[0048] It should be understood that other embodiments are possible in addition to those discussed above.For example, more generally, various aspects of the present invention relate to electrolytes for various electrochemical devices, including electrolytes comprising ion dissociative compounds.

[0049] As mentioned, in certain embodiments, the ion dissociation compound is present in the electrolyte in the electrochemical device. Without wishing to be bound by any theory, it is believed that the ion dissociation compound is a compound that can dissolve Li salts and / or help release, for example, those ions combined with ion pairs (e.g., lithium ions from lithium NMC compounds) and allow ions to enter the solution. Therefore, the ion dissociation compound is a compound that can increase the solubility limit of Li in solution relative to the absence of the ion dissociation compound in the solution. This can, for example, allow more ions to participate in the charge / discharge of the electrochemical device, as discussed below, which can lead to improvements such as electrolytes with increased oxidation potential, increased ionic conductivity, higher flash points or higher operating temperatures. Various compounds can be used as ion dissociation compounds. In some cases, the ion dissociation compound is an organic compound. Non-limiting examples of ion dissociation compounds include flame retardants, phosphates including organic phosphates, sulfones or polar aprotic solvents, etc.

[0050] For example, according to one set of embodiments, the ion dissociating compound comprises a sulfone. The sulfone may have the structure R 2 -SO2-R 1 , wherein each R can be the same or different. Each R can be, for example, a hydrocarbon chain such as an alkyl (substituted or unsubstituted), an alkenyl (substituted or unsubstituted) or an alkynyl (substituted or unsubstituted). The specific non-limiting example of sulfone includes divinyl sulfone, allyl methyl sulfone, diethylene sulfone or ethyl vinyl sulfone. In some cases, sulfones such as these can also be used as crosslinking agents, for example, because they contain double bonds, and thus for example for free radical polymerization. Other examples of sulfone include, but are not limited to, dimethyl sulfone, diphenyl sulfone, methyl phenyl sulfone, isopropyl sulfone, trimethylene sulfone, tetramethylene sulfone, diethyl sulfone or ethyl methyl sulfone, etc. In one group of embodiments, sulfone can be present with no more than 0.3wt%, no more than 0.2wt%, no more than 0.1wt%, etc.

[0051] In some cases, the ion dissociation compound can include polar solvents such as polar aprotic solvents. In some cases, for example, when polar aprotic solvents are used as electrolyte solvents, polar aprotic solvents can have high thermal stability and / or voltage stability. Aprotic solvents can lack OH bonds and NH bonds in some cases. Non-limiting examples of polar aprotic solvents include ethylene carbonate or sulfones such as those discussed herein. The polarity of the solvent can be between 1 and 5.5, for example, at least 1.5, at least 1.75, at least 2, at least 3, at least 4, at least 5 and / or no more than 5.5, no more than 4.5, no more than 3.5, no more than 2.5 or no more than 1.5 relative dipole moment polarity. Polar aprotic solvents can make ion solvation by their large dipole moments.

[0052] In another set of embodiments, the ionic dissociation compound includes a flame retardant. Various flame retardants are commercially available. Non-limiting examples of suitable flame retardants include nitrogen-containing flame retardants, silicon-containing flame retardants, fluorine-containing flame retardants (e.g., methyl difluoroacetate and ethyl difluoroacetate), composite flame retardant additives, or organophosphorus flame retardants (e.g., trialkyl phosphates such as triethyl phosphate or trimethyl phosphate), etc. In one set of embodiments, the flame retardant can be present in an amount not exceeding 0.3wt%, not exceeding 0.2wt%, not exceeding 0.1wt%, etc. One of ordinary skill in the art will be able to identify suitable flame retardants, for example, as discussed in Beard and Angeler, "Flame Retardants: Chemistry, Applications, and Environmental Impacts", Handbook of Combustion, 2010, or Hyung et al., "Flame-retardant additives for lithium-ion batteries", J. Power Sources, 119-121:383-387, 2003.

[0053] In some cases, flame retardants can be used to improve safety. For example, flame retardants with high boiling points (e.g., between 100°C and 300°C), high flash points (e.g., between 50°C and 250°C), low melting points (e.g., between -50°C and 70°C), high dielectric constants (e.g., between 1 and 80 at 25°C), good stability, and / or low cost can be selected. Flame retardants can also be used in some cases to prevent or inhibit fire and / or explosion caused by excessive temperature increases in the battery, for example.

[0054] In one set of embodiments, for example, as discussed herein, ionic dissociation compounds such as sulfones can be used in combination with various lithium salts or ions or other salts or ions. Examples of such lithium salts include, but are not limited to, lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), highly conductive lithium salts with anions having a strong tendency to provide fluorine. In some cases, the combination of lithium salts and ionic dissociation compounds can exhibit synergistic interface formation mechanisms such as CEI or SEI. In short, these interface formations can enable electrodes to be stably coupled. For example, according to certain embodiments, a stable formation of a graphite anode and a high-voltage cathode over an extended temperature range can be achieved.

[0055] In addition, the increased oxidation potential of the electrolyte, for example, associated with ionic dissociation compounds such as discussed herein, can provide enhanced stability in liquid and / or solid electrolytes in certain embodiments. The ionic dissociation compounds can include sulfones or other compounds such as described herein. Such electrolytes can, for example, be used for safer, longer life and / or higher voltage lithium batteries.

[0056] In some embodiments, electrolyte salts may be present. These may include alkali metal salts, such as lithium salts, sodium salts or magnesium salts. Specific non-limiting examples of lithium salts include LiTFSI, LiFSI, LiBOB, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, LiC(CF3SO2)3, LiDFOB, LiF, LiCl, LiBr, LiI, Li2SO4, LiNO3, Li3PO4, Li2CO3, LiOH, lithium acetate, trifluoromethyl lithium acetate, lithium oxalate, etc. Other examples include, but are not limited to, quaternary ammonium salts, quaternary phosphonium salts, transition metal salts or salts of protonic acids. Non-limiting examples of protonic acids include dimethyldioctadecyl ammonium chloride, tetraphenylphosphonium chloride, cobalt sulfate, lithium sulfate, lithium difluorophosphate (LiDFP or LiPO2F2), 2-trifluoromethyl-4,5-dicyanoimidazole lithium (LiTDI), etc.

[0057] In some cases, electrolyte salts such as those described herein can be present in a concentration of at least 1 M, at least 2 M, at least 3 M, at least 4 M, at least 5 M, at least 6 M, at least 7 M, at least 8 M, at least 9 M, at least 10 M, and / or no more than 10 M, no more than 9 M, no more than 8 M, no more than 7 M, no more than 6 M, no more than 5 M, no more than 4 M, no more than 3 M, no more than 2 M, no more than 1 M, etc. In some embodiments, combinations of any of these are also possible, for example, the electrolyte salt can be present at between 1 M and 3 M.

[0058] In one set of embodiments, the electrolyte salt may be present in an amount of at least 0.01, at least 0.03, at least 0.05, at least 0.1, at least 0.13, at least 0.15, at least 0.2, at least 0.23, at least 0.25, at least 0.3, at least 0.33, at least 0.35, at least 0.4, at least 0.43, at least 0.45, at least 0.5, at least 0.53, at least 0.55, at least 0.6, at least 0.63, at least 0.65, at least 0.7, and at least 0.8. / or a mole fraction of no more than 0.7, no more than 0.65, no more than 0.63, no more than 0.617, no more than 0.6, no more than 0.55, no more than 0.53, no more than 0.5, no more than 0.45, no more than 0.43, no more than 0.4, no more than 0.35, no more than 0.33, no more than 0.3, no more than 0.25, no more than 0.23, no more than 0.2, no more than 0.15, no more than 0.13, no more than 0.1, etc.

[0059] Controlling electrolyte salt concentration may be an effective strategy for obtaining certain functionalities of liquid electrolytes, including a wide electrochemical stability window. For example, electrolytes based on concentrated LiTFSI in organophosphates can be used to make Li + Ions can exhibit unusual capabilities in reversible cycling in carbonaceous electrodes. For example, enhanced solvation in high concentration electrolytes (HCEs) (e.g., in some cases, greater than 0.5 M, greater than 1.2 M, or greater than 3 M) can effectively stabilize ion dissociated compound molecules and promote the formation of salt-derived SEI that can mitigate anode and electrolyte degradation during extended cycles. Without wishing to be bound by any theory, it is believed that high concentration electrolytes can indicate that more ion dissociated compound molecules are coordinated with Li ions; since ion dissociated compound molecules can be reduced on the Li metal surface, the reduction of these free molecules can be beneficial to stabilize the Li metal surface.

[0060] In addition, in some cases, polymers may also be present. In some cases, such as those described herein, polymers may be present in an amount of at least 1 wt%, at least 2 wt%, at least 3 wt%, at least 4 wt%, at least 5 wt%, at least 6 wt%, at least 7 wt%, at least 8 wt%, at least 9 wt%, at least 10 wt%, at least 11 wt%, at least 12 wt%, at least 13 wt%, at least 14 wt%, at least 15 wt%, at least 16 wt%, at least 17 wt%, at least 18 wt%, at least 19 wt%, at least 20 wt%, at least 21 wt%, at least 22 wt%, at least 23 wt%, at least 24 wt%, at least 25 wt%, at least 26 wt%, at least 27 wt%, at least 28 wt%, at least 29 wt%, at least 30 wt%, at least 31 wt%, at least 32 wt%, at least 33 wt%, at least 34 wt%, at least 35 wt%, at least 36 wt%, at least 37 wt%, at least 38 wt%, at least 39 wt%, at least 40 wt%, at least 41 wt%, at least 42 wt%, at least 43 wt%, at least 44 wt%, at least 45 wt%, at least 46 wt%, at least 47 wt%, at least 48 wt%, at least 49 wt%, at least 50 wt%, at least 51 wt%, at least 52 wt%, at least 53 wt%, at least 54 wt%, at least 55 %, at least 35 wt%, at least 36 wt%, at least 37 wt%, at least 38 wt%, at least 39 wt%, at least 40 wt% and / or no more than 40 wt%, ... No more than 39wt%, no more than 38wt%, no more than 37wt%, no more than 36wt%, no more than 35wt%, no more than 34wt%, no more than 33wt%, no more than 32wt%, no more than 31wt%, no more than 30wt%, no more than 29wt%, no more than 28wt%, no more than 27wt%, no more than 26wt%, no more than 25wt%, no more than 24wt%, no more than 23wt%, no more than 22wt%, no more than 21wt%, no more than 20wt%, no more than 19wt%, no more than 18wt%, no more than 17wt%, no more than 16wt%, no more than 15wt%, no more than 14wt%, no more than 13wt%, no more than 12wt%, no more than 11wt%, no more than 10wt%, no more than 9wt%, no more than 8wt%, no more than 7wt%, no more than 6wt%, no more than 5wt%, no more than 4wt%, no more than 3wt%, no more than 2wt%, no more than 1wt% and the like.

[0061] Various polymers can be used. The polymer can include one or more copolymers. Although some polymers may not be conductive, it may be desirable for the polymer to be conductive. In some cases, more than one polymer may be present.

[0062] The molecular weight of polymer is not particularly limited, and can be any one of the molecular weights of a wide range. For example, the molecular weight can be at least 100, at least 200, at least 300, at least 500, at least 1,000, at least 3,000, at least 10,000, at least 30,000, at least 100,000, at least 300,000, at least 1,000,000, etc. In some cases, the molecular weight can be no more than 10,000,000, no more than 3,000,000, no more than 1,000,000, no more than 300,000, no more than 100,000, no more than 30,000, no more than 10,000, no more than 3,000, no more than 1,000, no more than 500, no more than 300, etc. Any combination of these is also possible, for example, the molecular weight can be between 200 and 1,000. The molecular weight can be determined as the number average molecular weight.

[0063] Non-limiting examples of polymers include poly(ethylene) (PE), poly(ethylene oxide) (PEO), poly(propylene) (PP), poly(propylene oxide), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), poly(bis(methoxyethoxyethoxy)-phosphazene), poly(dimethylsiloxane) (PDMS), cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyvinylidene fluoride (PVdF), polyvinyl pyrrolidone (PVP), polystyrene, sulfonates (PSS), poly(vinylidene chloride), polypropylene oxide, polyvinyl acetate, polytetrafluoroethylene (e.g., Teflon), poly(p-butylene sulfonate), polyvinyl acetate, polytetrafluoroethylene (e.g., Teflon), poly(p-butylene sulfonate), polyvinyl acetate, polyvinyl acetate, polytetrafluoroethylene (e.g., Teflon), poly(p-butylene sulfonate), polyvinyl acetate, polyvinyl acetate, polyvinyl chloride, polyvinyl acetate ... Polyethylene terephthalate (PET), polyimide, polyhydroxyalkanoate (PHA), copolymers containing PEO (e.g., polystyrene (PS)-PEO copolymers and poly(methyl methacrylate) (PMMA)-PEO copolymers), poly(acrylonitrile-co-methacrylate), copolymers containing PVdF (e.g., polyvinylidene fluoride-co-hexafluoropropylene (PVdF-co-HFP), or PMMA copolymers (e.g., poly(methyl methacrylate-co-ethyl acrylate)), etc. Derivatives of any of these may also be included. In various examples, the polymer material is a combination of two or more of these polymers.

[0064] Polymer can have various structures (e.g., secondary structure). In various examples, polymer can be non-crystalline, crystalline or a combination thereof. In some embodiments, polymer and / or copolymer can be expected to have low crystallinity. For example, the crystallinity can be less than 70%, less than 60%, less than 50%, less than 40% or less than 30%. Crystallinity can be measured, for example, using DSC by comparing the exothermic energy of the crystallization process of a semi-crystalline polymer with the energy of a complete crystal calculated based on crystallization.

[0065] In some cases, due to in polymer, for example, in the skeleton structure of polymer, add functional groups such as urea moiety and / or carbamate moiety, so polymer can show improved properties.In some cases, urea moiety and / or carbamate moiety can be cross-linked together, and / or cross-linked with other polymers, for example, as described herein.In the case of not wishing to be bound by any theory, it is believed that groups such as urea, urethane or carbamate include hydrogen bond donors and acceptors, which can lead to improvements in properties such as mechanical properties and / or electrochemical properties, for example, as discussed herein.For example, urea linking groups with rigid bonding can contribute to improving mechanical strength.In addition, hydrogen bonds can contribute to dissociation of lithium salts, which can lead to improved ionic conductivity.

[0066] In some embodiments, groups such as urea, urethane or carbamate can be present in the backbone of the polymer, for example, as a linking group between the intermediate polymer fragment and two acrylic acid series terminals. During polymer formation, different functional groups such as amine and carbamate or alcohol and isocyanate can be used to provide urea and / or carbamate in the polymer. Such groups can exist adjacent to each other, and / or some groups can be separated by spacer groups, for example, between urea and / or carbamate and acrylate.

[0067] Non-limiting examples of polymers include those produced by polymerizing one or more of the following polymer precursors and / or other precursors:

[0068]

[0069] In these structures, R1 can be selected so as to coordinate with a salt or ion, for example, to produce a polymer / salt complex that can be used as an electrolyte. For example, R1 can include a charged portion, and / or a portion that is uncharged but, for example, is easily ionized to produce a charge at an acidic or alkaline pH (e.g., at a pH of less than 5, less than 4, less than 3, or less than 2, or greater than 9, greater than 10, greater than 11, or greater than 12). Specific examples of R1 include, but are not limited to, the following (where * indicates a point of attachment):

[0070]

[0071] In addition, in some cases, 2, 3, 4 or more of the following may be present simultaneously in the R1 structure, for example, as a copolymer. For example, they may be present in alternating, block, random or other copolymer structures to define the R1 portion. In some cases, 2, 3, 4 or more polymers may be present and in some cases may be cross-linked together, for example, as discussed herein.

[0072] In these structures, n and / or m (if applicable) can each be an integer. In some cases, n and / or m can each be less than 100,000, less than 50,000, less than 30,000, less than 10,000, less than 5,000, less than 3,000, less than 1,000, less than 500, etc. In some cases, n and / or m can be at least 1, at least 3, at least 5, at least 10, at least 30, at least 50, at least 100, at least 300, at least 500, at least 1,000, at least 3,000, at least 5,000, at least 10,000, at least 30,000, at least 50,000, etc. Combinations of any of these ranges are possible; as non-limiting examples, n can be an integer between 1 and 10,000, m can be an integer between 1 and 5,000, n can be an integer between 1,000 and 5,000, m can be an integer between 500 and 1,000, etc.

[0073] In these structures, R2, R3, R4, R5 and R6 (if applicable) can be independently selected to make the polymer symmetrical or asymmetrical. Examples of R2, R3, R4, R5 and R6 include, but are not limited to, one of the following structures:

[0074]

[0075] Other examples of R2, R3, R4, R5 and R6 include, but are not limited to, acrylate, ethylene oxide, ethylene oxide, isocyanate, cyclic carbonate, lactone, lactam, vinyl (CH2=CH-) or vinyl derivatives (i.e., wherein 1, 2 or 3 H in the CH2=CH-structure have been replaced by F or Cl). Non-limiting examples of cyclic carbonate include ethylene carbonate, propylene carbonate, fluoroethylene carbonate, etc. In addition, it should be understood that these end groups are provided only by way of example. Usually, end groups are not important because they usually do not affect performance in a significant manner.

[0076] In addition, in one set of embodiments, functional groups such as urea and / or carbamate can be cross-linked together, for example, as described herein. For example, such functional groups can be cross-linked together using ultraviolet light, thermoforming, or exposure to elevated temperatures (e.g., temperatures between 20° C. and 100° C.), or other methods including those described herein. In some cases, the introduction of urea or carbamate functional groups can improve mechanical properties or electrochemical performance, such as relatively high ionic conductivity, ion migration number, decomposition voltage, or tensile strength, etc.

[0077] In one set of embodiments, the polymer can be present in a mole fraction of at least 0.01, at least 0.02, at least 0.027, at least 0.03, at least 0.05, at least 0.1, at least 0.11, at least 0.12, at least 0.13, at least 0.15, at least 0.2, at least 0.21, at least 0.22, at least 0.23, at least 0.25, at least 0.3, and / or no more than 0.3, no more than 0.25, no more than 0.32, no more than 0.22, no more than 0.21, no more than 0.2, no more than 0.15, no more than 0.13, no more than 0.12, no more than 0.11, no more than 0.1, no more than 0.05, no more than 0.03, no more than 0.02, no more than 0.01, etc.

[0078] Furthermore, as discussed, more than one polymer may be present, for example, as a physical blend and / or as a copolymer, etc., including any combination of these polymers and / or other polymers.

[0079] Other examples of polymers include those described in U.S. Patent Application Serial No. 16 / 240,502, filed on January 4, 2019, entitled “Polymer Solid Electrolytes,” which is incorporated herein by reference in its entirety.

[0080] In one group of embodiments, polymer includes plasticizer, which can be used to improve the processability and / or control ionic conductivity and mechanical strength of polymer. For example, plasticizer can be polymer, small molecule (that is, molecular weight is less than 1kDa), nitrile, oligoether (for example, triethylene glycol dimethyl ether), cyclic carbonate or ionic liquid etc. Non-limiting examples of potential suitable plasticizer include ethylene carbonate, succinonitrile, cyclopentane sulfone or phosphate etc. Non-limiting examples of nitrile include succinonitrile, glutaronitrile, adiponitrile and / or malononitrile. Non-limiting examples of cyclic carbonate include ethylene carbonate, propylene carbonate, fluoroethylene carbonate etc. Non-limiting examples of ionic liquid include N-propyl-N-methylpyrrolidinium bis (fluorosulfonyl) imide or 1-ethyl-3-methylimidazolium bis (fluorosulfonyl) imide. Other non-limiting examples of plasticizer include polymers such as polyethylene oxide, polycarbonate, polyacrylonitrile or polylactic acid. In some cases, the plasticizer can be a relatively hydrophilic (e.g., water contact angle less than 90°) polymer. In addition, the polymer may be sulfur-free. Other examples of plasticizers include those described in U.S. Patent Application Serial No. 16 / 240,502, filed on January 4, 2019, entitled “Polymer Solid Electrolyte,” which is incorporated herein by reference in its entirety.

[0081] In some embodiments, the plasticizer may be present in an amount of at least 0.1, at least 0.11, at least 0.12, at least 0.13, at least 0.15, at least 0.2, at least 0.22, at least 0.23, at least 0.25, at least 0.287, at least 0.3, at least 0.31, at least 0.32, at least 0.33, at least 0.35, at least 0.4, at least 0.5, at least 0.6, at least 0.7, at least 0.8, at least 0.9, at least 0.93, at least 0.95, and / or no more than 0.95, no more than 0.96, no more than 0.97, no more than 0.98, no more than 0.99, no more than 0.10, no more than 0.11, no more than 0.12, no more than 0.13, no more than 0.15, no more than 0.28 There are mole fractions exceeding 0.93, not more than 0.916, not more than 0.9, not more than 0.8, not more than 0.7, not more than 0.6, not more than 0.5, not more than 0.4, not more than 0.35, not more than 0.33, not more than 0.32, not more than 0.31, not more than 0.3, not more than 0.25, not more than 0.32, not more than 0.22, not more than 0.21, not more than 0.2, not more than 0.15, not more than 0.13, not more than 0.12, not more than 0.11, not more than 0.1, etc.

[0082] In one set of embodiments, the molar ratio of (polymer + cross-linkable oligomer) to plasticizer in the solid electrolyte can be at least 1:0.2, at least 1:0.5, at least 1:1, at least 1:1.5, at least 1:2, at least 1:3, at least 1:5 and / or no more than 1:5, no more than 1:3, no more than 1:2, no more than 1:1.5, no more than 1:1, no more than 1:0.5, or no more than 1:0.2, and combinations of any of these are also possible, for example, the ratio of (polymer + cross-linkable oligomer) to plasticizer can be between 2:1 and 1:2.

[0083] In addition, in certain embodiments, additives or other compounds may also be present, such as cathode protectants, anode protectants, antioxidants, inorganic additives, etc. Non-limiting examples of inorganic additives include Al2O3, SiO2, SiO x 、TiO2、Li3PS4、Li 10 GeP2S 12 、Li7La3Zr2O 12 , Li 6.4 LqCy 1.4 Ta 0.6 O 12 、LiLaTiO3、Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1.3 Al 0.3 Ge 1.7(PO4)3, etc. An example of a cathodic protectant is LiDFOB (lithium difluoro(oxalato)borate). An example of an anodic protectant is fluoroethylene carbonate. An example of an antioxidant is LiBOB (lithium bis(oxalate)borate). Other similar compounds will be known to those of ordinary skill in the art. These may be added for a variety of reasons, for example, to improve other performance indicators such as cyclability. In some cases, inorganic additives may be used that typically contain electronegative atoms such as oxygen that can attract cations. Thus, for example, compared to anions, such as Li + Plasma can be repositioned relatively easily.

[0084] In another group of embodiments, the solid electrolyte may include an organic carbonate additive. Without wishing to be bound by any theory, in addition to the solid electrolyte interface (SEI) with lower resistance, the organic carbonate can significantly enhance the wettability of the electrode in the corresponding electrolyte, which can improve the battery performance to achieve higher capacity compared to the electrolyte without any organic carbonate additive. For example, organic carbonate can show stability at negative potential. In some cases, organic carbonate can extend the electrochemical stability of the electrolyte to negative potential. For example, a small amount of organic carbonate can significantly improve the battery performance of polymer solid electrolytes, because the presence of organic additives can increase ion mobility by reducing lithium coordination, and the electrolyte is still non-flammable.

[0085] Non-limiting examples of organic carbonate additives include ethylene carbonate (EC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), di-(2,2,2 trifluoroethyl) carbonate, methylene-ethylene carbonate (MEC), 1,2-dimethoxyethane carbonate (DME), diethylene carbonate (DEC), (4R, 5S)-4,5-difluoro-1,3-dioxolane-2-one (DiFEC). More than one organic carbonate additive including these and / or other additives is also possible. The organic carbonate may be present in an amount not exceeding 15wt% of the solid electrolyte, not exceeding 10wt% of the solid electrolyte, not exceeding 5wt% of the solid electrolyte, etc.

[0086] Non-limiting examples of other additives include sulfite additives, sulfate additives and sultone additives (ethylene sulfite, vinyl ethylene sulfite, propenyl-1,3-sultone (prop-1-ene-1,3-sultone), trimethylene sulfate, etc.). Ether additives or fluoroether additives. Anhydrides (glutaric anhydride, succinic anhydride, etc.), InF3, tris (2,2,2-trifluoroethyl) borate. Ionic or nonionic fluorinated surfactants. As discussed in Atetegeb Meazah Haregewoin et al., "Electrolyte additives for lithium ion battery electrodes: progress and perspectives," Energy Environ. Sci., 2016, 9, 1955-1988, or Dr. Heng Zhang et al., "Electrolyte Additives for Lithium Metal Anodes and Rechargeable Lithium Metal Batteries: Progress and Perspectives," Angew. Chem. Int. Ed. 2018, 57, 15002-15027.

[0087] In one set of embodiments, the electrolyte further comprises a stabilizing additive. Non-limiting examples of stabilizing additives include lithium bis(oxalato)borate (LiBoB) or LiBF4, etc. In one set of embodiments, the stabilizing additive may be present at no more than 0.3wt%, no more than 0.2wt%, no more than 0.1wt%, etc. Without wishing to be bound by any theory, the stabilizing additive may be used in certain embodiments to maintain the voltage of the polymer electrolyte; as a non-limiting example, the electrolyte may not be able to maintain a voltage of more than 3.9V, but a stabilizing additive may be used to maintain a voltage of at least 4.4V.

[0088] In some embodiments, the electrolyte may further include an initiator such as a stable initiator. Non-limiting examples include benzoyl peroxide, 2,2'-azobisisobutyronitrile (AIBN), 4,4-azobis(4-cyanovaleric acid) (ACVA) or potassium persulfate, etc. Other examples include Irgacure initiator, 2,2'-azobis(2-methylpropionitrile), ammonium persulfate, or other initiators known to those of ordinary skill in the art. In some embodiments, an initiator can be used to initiate a crosslinking reaction within a polymer, or to promote polymerization in other ways. Those of ordinary skill in the art will know other initiators that can be used, as well as these initiators and / or combinations with these initiators. Many initiators are easily commercially available. In one set of embodiments, the initiator can be present in an amount not exceeding 0.3wt%, not exceeding 0.2wt%, not exceeding 0.1wt%, etc. In some cases, an initiator can be added so that the mole fraction is between 0.001 and 0.01, or other appropriate mole fractions to promote polymerization.

[0089] In some embodiments, the electrolyte may further include a phosphine additive. Non-limiting examples of phosphine additives include hexafluoroisopropyl triphosphate or triisopropylethylsulfonyl (pentafluorophenyl) phosphine, etc. In one set of embodiments, the phosphine additive may be present in an amount of no more than 0.3 wt%, no more than 0.2 wt%, no more than 0.1 wt%, etc.

[0090] In some embodiments, the electrolyte may further include an ether additive. The ether additive may be a linear polymer that contributes to ion transport in some cases. For example, the ether additive may increase the conductivity of the solid electrolyte. Non-limiting examples of ether additives include hydrofluoroether, 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, bis (2,2,2-trifluoroethyl) ether, oligoethylene glycol methyl ether, tetraglyme, bis (2,2,2-trifluoroethyl) ether, oligoethylene glycol methyl ether, etc. In one group of embodiments, the ether additive may be present with no more than 0.3wt%, no more than 0.2wt%, no more than 0.1wt%, etc.

[0091] Non-limiting examples of other suitable additives include: oligoethylene glycols, carbonates such as 1,2-dimethoxyethane carbonate, fluoroethylene carbonate, vinylene carbonate, etc., (4R,5S)-4,5-difluoro-1,3-dioxolane-2-one, methylene-ethylene carbonate, propenyl-1,3-sultone, succinic anhydride.

[0092] Some additives such as ethylene carbonate (EC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), (4R, 5S) -4,5-difluoro-1,3-dioxolane-2-one (DiFEC), methylene-ethylene carbonate (MEC), propenyl-1,3-sultone (PES) and / or succinic anhydride (SA) can preferentially decompose and undergo polymerization and ion exchange reactions at the anode / electrolyte interface to produce a solid-electrolyte-interface (SEI) with desired chemical composition and physical properties. Without wishing to be bound by any theory, in some cases, a stable SEI can conform to cyclic volume changes at the anode during charging (addition) and discharging (removal) of metal atoms to the electrode.

[0093] In some cases, additives such as those described herein can be present in a weight percentage of at least 1 wt%, at least 2 wt%, at least 3 wt%, at least 4 wt%, at least 5 wt%, at least 6 wt%, at least 7 wt%, at least 8 wt%, at least 9 wt%, at least 10 wt%, at least 11 wt%, at least 12 wt%, at least 13 wt%, at least 14 wt%, at least 15 wt%, at least 16 wt%, at least 17 wt%, at least 18 wt%, at least 19 wt%, at least 20 wt%, and / or no more than 20 wt%, no more than 19 wt%, no more than 18 wt%, no more than 17 wt%, no more than 16 wt%, no more than 15 wt%, no more than 14 wt%, no more than 13 wt%, no more than 12 wt%, no more than 11 wt%, no more than 10 wt%, no more than 9 wt%, no more than 8 wt%, no more than 7 wt%, no more than 6 wt%, no more than 5 wt%, no more than 4 wt%, no more than 3 wt%, no more than 2 wt%, no more than 1 wt%, no more than 1 wt%, and the like.

[0094] In some cases, electrolytes such as those described herein can provide certain beneficial properties, such as surprisingly high ionic conductivity compared to other solid electrolytes. For example, polymer solid electrolytes can exhibit at least 10 -8 S / cm, at least 2×10 -8 S / cm, at least 3×10 -8 S / cm, at least 5×10 -8 S / cm, at least 10 -7 S / cm, at least 2×10 -7 S / cm, at least 3×10 -7 S / cm, at least 5×10 -7 S / cm, at least 10 -6 S / cm, at least 2×10 -6 S / cm, at least 3×10 -6 S / cm, at least 5×10-6 S / cm, at least 10 -5 S / cm, at least 2×10 -5 S / cm, at least 3×10 -5 S / cm, at least 5×10 -5 S / cm, at least 10 -4 S / cm, at least 0.8×10 -4 S / cm, at least 1.1×10 -4 S / cm, at least 1.2×10 -4 S / cm, at least 1.4×10 -4 S / cm, at least 1.6×10 -4 S / cm, at least 2×10 -4 S / cm, at least 3×10 -4 S / cm, at least 5×10 -4 S / cm, at least 10 -3 S / cm, at least 2×10 -3 S / cm, at least 3×10 -3 S / cm, at least 5×10 -3 S / cm, etc. In one embodiment, for example, the ionic conductivity of the polymer solid electrolyte is 2.1×10 -6 S / cm to 5.2×10 -6 In another embodiment, the ionic conductivity can be between 10 -8 S / cm to 10 -2 S / cm. Without wishing to be bound by any theory, it is believed that if the physical integrity of the polymer solid electrolyte is ensured by using a small amount of polymer, liquid level ionic conductivity can be achieved. The ionic conductivity can be determined, for example, using a 2032 button cell, stainless steel as the working electrode and Li metal as the reference electrode, wherein the ionic conductivity is calculated from the bulk resistance in the impedance spectrum in a constant potential mode at a scanning frequency of 1 MHz to 1 Hz.

[0095] As another example, the electrode may exhibit at least 1 mA h / cm 2 , 1.5mA h / cm 2 , 2mA h / cm 2 、2.5mAh / cm 2 、3mA h / cm 2 、3.5mA h / cm 2 , 4mA h / cm 2 、4.5mAh / cm 2 , 5mA h / cm 2 、5.5mA h / cm 2 、6mA h / cm2 The mass loading of the electrode is a measure of the design area capacity of the electrode. The area is the area of ​​the electrode. This can be determined, for example, by weighing the electrode, calculating the active material content of the electrode (e.g., the number of ions it can contain), and then calculating the design capacity based on the active material content.

[0096] In addition, in some embodiments, electrolytes such as those recorded herein can provide relatively high oxidation potentials. Electrolytes with relatively high oxidation potentials can be particularly useful, for example, in the purposes requiring higher voltages. In some cases, the oxidation potential of polymer solid electrolytes can be at least 0.3V, at least 0.4V, at least 0.5V, at least 0.6V, at least 0.7V, at least 0.8V, at least 0.9V, at least 1V, at least 1.5V, at least 2V, at least 2.5V, at least 3V, at least 3.5V, at least 3.8V, at least 4V, at least 4.5V, at least 5.0V, at least 5.1V or at least 5.5V. Standard techniques known to those of ordinary skill in the art such as cyclic voltammetry can be used to measure oxidation potentials. In the case of not wishing to be bound by any theory, it is believed that the electrolyte with high oxidation potential can be relatively stable at high voltages.

[0097] In addition, in some embodiments, electrolytes such as those described herein can provide relatively high flash points. Flash point is the temperature at which a material (e.g., electrolyte) will burn if an ignition source (e.g., flame or spark) is given. Electrolytes with relatively high flash points are particularly useful, for example, in applications requiring higher flash points. In some cases, the flash point of an electrolyte can be at least 85°C, at least 90°C, at least 93.3°C, at least 95°C, at least 100°C, at least 105°C, at least 110°C, at least 115°C, at least 120°C, at least 125°C, at least 130°C, at least 135°C, at least 140°C, at least 145°C, at least 150°C, at least 155°C, at least 160°C, at least 165°C, at least 170°C, at least 175°C, at least 180°C, at least 185°C, at least 190°C, at least 195°C, at least 200°C, etc. Flash point can be determined using standard techniques known to those of ordinary skill in the art. Without wishing to be bound by any theory, it is believed that electrolytes with relatively high flash points may be used at elevated temperatures, which may help improve the safety of the electrolyte.

[0098] In addition, in some embodiments, electrolytes such as those described herein can be used or operated at relatively high temperatures, for example, at least 85°C, at least 90°C, at least 93°C, at least 95°C, at least 100°C, at least 105°C, at least 110°C, at least 115°C, at least 120°C, at least 125°C, at least 130°C, at least 135°C, at least 140°C, at least 145°C, at least 150°C, at least 155°C, at least 160°C, at least 165°C, at least 170°C, at least 175°C, at least 180°C, at least 185°C, at least 190°C, at least 195°C, at least 200°C, etc. In some cases, the electrolyte can be highly stable at relatively high temperatures. The operating temperature of the electrolyte can be controlled by other parameters such as its electrochemical stability at elevated temperatures. The operating temperature can be lower than the flash point.

[0099] To determine the operating temperature, the battery can be tested at room temperature (25°C), where m is the number of cycles at which the capacity is 80% of the capacity after the first cycle. The battery can then be tested at an operating temperature T; for example, the battery can be tested in an oven at a temperature of T, where n is the number of cycles at which the capacity is 80% of the capacity after the first cycle. The operating temperature is the highest temperature at which the battery still satisfies the formula 0.3≤n / m≤1. For example, n / m can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc.

[0100] In some aspects, the present invention generally relates to an electrochemical unit, such as in an electrochemical device, comprising an electrolyte material such as those discussed herein. Non-limiting examples of electrochemical devices include batteries, capacitors, sensors, relays, electrochromic elements, or photoelectric conversion elements, etc. In one set of embodiments, the electrochemical device is a battery, such as an ion conductive battery. Non-limiting examples of ion conductive batteries include lithium ion conductive batteries, sodium ion conductive batteries, and magnesium ion conductive batteries, etc. For example, a lithium ion battery may include one or more lithium ion electrochemical units, some or all of which have structures such as described herein. In some cases, the battery is a solid-state battery. The electrochemical device may also include an anode, a cathode, a separator, etc. Many of these are commercially available. The electrolyte as described herein may be used alone and / or in combination with other electrolyte materials as an electrolyte for an electrochemical device.

[0101] The anode material can be a conductive material. For example, the anode can include conductive carbon materials, such as graphite, hard carbon and porous hollow carbon balls and tubes. Other non-limiting examples of conductive materials include conductive carbon materials, tin and its alloys, tin / carbon, tin / cobalt alloys and silicon / carbon materials. Non-limiting examples of conductive carbon materials include graphite, hard carbon and porous hollow carbon balls and tubes (e.g., carbon nanotubes). As other examples, the anode can include silicon, tin, carbon, phosphorus, Li, Gr, Si, Si / Gr, Sn (alloy anode), or Li4Ti5O 12 Anodes, etc. A variety of anodes and anode materials are commercially available.

[0102] In some embodiments, the anode can be a metal. Non-limiting examples of metals include lithium metal, sodium metal, and magnesium metal, among others. Lithium (Li) metal is a promising anode material for high energy density storage systems because of its high specific capacity (3860 mA h g) relative to a standard hydrogen electrode. -1 ) and a low reduction potential (-3.04 V).

[0103] In one embodiment, the anode may include, for example, lithium metal, lithium carbide, Li6C, or lithium titanate (e.g., Li4Ti5O 12 ) and other lithium ion conductive materials. In another embodiment, the anode material may include, for example, sodium metal, Na2C8H4O4 or Na 0.66 Li 0.22 Ti 0.78 In another embodiment, the anode material may include a sodium ion conductive material such as magnesium metal.

[0104] In certain embodiments, the cathode can include one or more electroactive materials. A variety of electroactive materials can be used, including lithium ion conductive materials.

[0105] In some cases, the cathode may include one or more particles. In some cases, the particles may include one or more positive electrode electroactive materials. The particles may include positive ions such as lithium, sodium or magnesium. Examples of particles for cathodes can be found in U.S. Patent Application Serial No. 16 / 512,502, entitled "Electrodes for Lithium Ion Batteries and Other Uses," which is incorporated herein by reference in its entirety.

[0106] In one set of embodiments, the cathode may include lithium, which may be present, for example, as lithium metal and / or a lithium salt. Non-limiting examples include lithium cobalt oxide (LCO), lithium nickel manganese cobalt oxide (NMC) (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 or LiNi 0.5 Co 0.2 Mn0.3 O2), lithium nickel cobalt manganese aluminum oxide, lithium nickel cobalt aluminum oxide, lithium titanate, metallic lithium, lithium metal oxide, lithium cobalt oxide, lithium manganese oxide (LMO) (e.g., LiMn2O4 and LiNi 0.5 Mn 1.5 O4), lithium iron phosphate (LFP) (e.g., LiFePO4), LiMnPO4, LiCoPO4 (LCP), Li2MMn3O8, wherein M is Fe and / or Co, layered Li-Ni-Co-Mn oxide (NCM) and layered Li-Ni-Co-Al oxide (NCA), etc. LiMnPO4, LiCoPO4, LiNIPO4, Li3V2(PO4)3, LiVOPO4, LiVOPO4F, LiCoPO4F, LiCoSO4F, Li2VOP2O7, LiMnSiO4, LiFePO4, lithium manganese oxide (spinel LiMn2O4, layered Li2MnO3, layered LiMnO2) and S, FeS2. Combinations of these and / or other compounds are also possible.

[0107] As a non-limiting example, the cathode may include a positive electrode electroactive material comprising various amounts of lithium, nickel, manganese, and cobalt. x Mn y Co z In some cases, the sum of x, y and z is 1, i.e., in addition to these three ions, no other ions (except alkali metal ions, e.g., lithium) are present in the NMC matrix composition. Therefore, z can be equal to (1-xy). However, in other cases, the sum of x, y and z can actually be less than or greater than 1, e.g., from 0.8 to 1.2, from 0.9 to 1.1, from 0.95 to 1.05, or from 0.98 to 1.02. Other example values ​​are discussed below. Therefore, the material may be overdoped or underdoped in some cases, and / or contain other ions present in addition to nickel, manganese and cobalt.

[0108] As an example, the expression of the positive electrode electroactive material can be Li a (Ni x Mn y Co z )02. In some cases, a is a value in a first range between about 1.00 and 1.01, x is a value in a second range between about 0.34 and 0.58, y is a value in a third range between about 0.21 and 0.38, and z is a value in a fourth range between about 0.21 and 0.38. Other example values ​​for each of a, x, y, and z are discussed below.

[0109] In another set of embodiments, the positive electrode electroactive material may include an electroactive composition comprising lithium (Li), nickel (Ni), manganese (Mn) and cobalt (Co). The positive electrode electroactive material may further include an element M selected from samarium (Sm), lanthanum (La), zinc (Zn) or a combination thereof. In some embodiments, the composition may be expressed as Li a M b (Ni x Mn y Co z ) 1-b In some cases, a can be a value within a first range between about 1.00 and 1.01, b can be a value within a second range between about 0 and 0.08, x can be a value within a third range between about 0.34 and 0.58, y can be a value within a fourth range between about 0.21 and 0.38, and z can be a value within a fifth range between about 0.21 and 0.38. Other example values ​​for each of a, b, x, y, and z are discussed below.

[0110] In any of the structures described above or herein, in some cases, x (e.g., nickel) can be at least 0.5, at least 0.55, at least 0.6, at least 0.65, at least 0.7, at least 0.75, at least 0.8, at least 0.85, at least 0.9, at least 0.95, etc. In some embodiments, x can be no more than 0.95, no more than 0.9, no more than 0.85, no more than 0.8, no more than 0.75, no more than 0.7, no more than 0.65, no more than 0.6, no more than 0.55, no more than 0.5, etc. In certain embodiments, any combination of these is possible. For example, x can be between 0.7 and 0.9.

[0111] In some cases, y (e.g., manganese) can be at least 0.05, at least 0.1, at least 0.15, at least 0.2, at least 0.25, at least 0.3, at least 0.35, at least 0.4, at least 0.45, at least 0.5, etc. In some embodiments, y can be no more than 0.5, no more than 0.45, no more than 0.4, no more than 0.35, no more than 0.3, no more than 0.25, no more than 0.2, no more than 0.15, no more than 0.1, no more than 0.05, etc. In certain embodiments, any combination of these is possible. For example, y can be between 0.05 and 0.15.

[0112] In some cases, z (e.g., cobalt) can be at least 0.05, at least 0.1, at least 0.15, at least 0.2, at least 0.25, at least 0.3, at least 0.35, at least 0.4, at least 0.45, at least 0.5, etc. In some embodiments, z can be no more than 0.5, no more than 0.45, no more than 0.4, no more than 0.35, no more than 0.3, no more than 0.25, no more than 0.2, no more than 0.15, no more than 0.1, no more than 0.05, etc. In certain embodiments, any combination of these is possible. For example, z can be between 0.05 and 0.15.

[0113] In some cases, a (e.g., lithium) can be at least 0.95, at least 0.96, at least 0.97, at least 0.98, at least 0.99, at least 1.00, at least 1.01, at least 1.02, at least 1.03, at least 1.04, at least 1.05, etc., and / or no more than 1.05, no more than 1.04, no more than 1.03, no more than 1.02, no more than 1.01, no more than 1.00, no more than 0.99, no more than 0.98, no more than 0.97, no more than 0.96, no more than 0.95, etc. Combinations of any of these are also possible, for example, a can be between 0.99 and 1.03.

[0114] In some cases, b can be at least 0.01, at least 0.02, at least 0.03, at least 0.04, at least 0.05, at least 0.06, at least 0.07, at least 0.08, at least 0.09, at least 0.1, etc. In some embodiments, b can be no more than 0.1, no more than 0.09, no more than 0.08, no more than 0.07, no more than 0.06, no more than 0.05, no more than 0.04, no more than 0.03, no more than 0.02, no more than 0.01. In some cases, b can also be 0. Combinations of any of these are also possible, for example, a can be between 0.07 and 0.09.

[0115] Other examples of positive electrode electroactive materials can be found in International Patent Application Publication No. WO 2018 / 112182, entitled “Electroactive Material for Lithium-Ion or other Batteries”, or International Patent Application Publication No. WO 2017 / 053275, entitled “Nickel-Based Positive Electroactive Materials”, each of which is incorporated herein by reference in its entirety.

[0116] On the other hand, the present disclosure generally relates to methods for preparing electrolytes such as those discussed herein. For example, in one set of embodiments, a solid electrolyte can be prepared by mixing a liquid electrolyte and a polymer precursor into a cell and curing the liquid electrolyte in the cell to form a solid electrolyte. The electrolyte and polymer precursor can be as discussed herein. For example, the electrolyte can include a lithium salt and an ion dissociation compound. In some cases, the liquid electrolyte and a monomer or polymer can be mixed in a liquid phase and introduced into a preassembled cell. The curing in the cell can occur based on thermal gelation, physical gelation, polymerization or crosslinking, for example, to form a solid electrolyte in the cell.

[0117] In some cases, polymers can be produced by reacting various monomers together. Non-limiting examples of monomers include structures described herein, for example, different combinations of methacrylate monomers (e.g., norbornyl methacrylate) with different ester groups. Other examples of esters include, but are not limited to, methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-aminoethyl methacrylate hydrochloride, glycidyl methacrylate, 2-(ethylamino)ethyl methacrylate, and the like.

[0118] In some cases, for example, to promote polymerization, an initiator may be present. For example, the initiator may include a chemical initiator such as Irgacure initiator, 2,2'-azobis(2-methylpropionitrile), ammonium persulfate, or other initiators known to those of ordinary skill in the art. In some cases, the initiator may be added to provide a mole fraction between 0.001 and 0.01 or other suitable mole fractions to promote polymerization.

[0119] In one set of embodiments, the polymer can be mixed with a solvent to form a slurry, which can be cured to form a solid. In addition, in some cases, more than one polymer can be present in the slurry, for example, a first polymer and a second polymer can be added to the slurry sequentially, simultaneously, etc. The polymers can each independently be a polymer such as those described herein and / or other suitable polymers.

[0120] The limiting examples of suitable solvents include solvents such as water (e.g., distilled water), methanol, ethanol or other aqueous solvents. Other examples of solvents include organic solvents such as pyridine or chloroform. In some cases, more than one such solvent may be present. In addition, after forming the slurry, the solvent may be removed, for example, via techniques such as evaporation.

[0121] In addition, in some cases, a plasticizer may also be present, for example, such as succinonitrile, ethylene carbonate, cyclopentane or trimethyl phosphate. In addition, in some embodiments, an electrolyte salt may also be present, for example, a salt of an alkali metal such as lithium or sodium. Specific non-limiting examples of lithium salts include LiTFSI, LiFSI, LiBOB, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, LiC(CF3SO2)3, LiDFOB, LiF, LiCl, LiBr, LiI, Li2SO4, LiNO3, Li3PO4, Li2CO3, LiOH, lithium acetate, trifluoromethyl lithium acetate, lithium oxalate, etc., or other salts such as those described herein.

[0122] In some embodiments, the slurry can be cured to form a film such as a solid film. For example, the mixture can be formed into a film by curing, such as using UV light, thermoforming, or exposure to elevated temperatures. For example, curing can be initiated by exposure to UV light for at least 3 min, at least 5 min, at least 10 min, at least 15 min, etc. and / or by exposure to a temperature of at least 20°C, at least 30°C, at least 40°C, at least 50°C, at least 60°C, at least 70°C, at least 80°C, at least 90°C, at least 100°C, etc. As an example, the slurry can be coated or placed on a surface and / or in a mold and exposed to UV light to cure the polymer.

[0123] In addition, in some cases, during the curing process, at least some of the polymers may also be crosslinked, e.g., as discussed herein, which in some cases may improve mechanical properties and / or electrochemical performance. For example, exposure to UV light may facilitate the crosslinking process. As another example, thermal crosslinking may be used.

[0124] Additional discussion of electrolyte fabrication may be found in International Patent Application Publication No. WO 2018 / 112182, entitled “Electroactive Materials for Lithium Ion or Other Batteries,” or International Patent Application Publication No. WO 2017 / 053275, entitled “Nickel-Based Positive Electroactive Materials,” each of which is incorporated herein by reference in its entirety for all purposes.

[0125] The following documents are incorporated herein by reference in their entirety: International Patent Application Serial No. PCT / US16 / 52627, entitled “High Performance Nickel-Based Positive Electroactive Material for a Lithium-Ion Battery”, published as International Patent Application Publication No. WO 2017 / 053275; International Patent Application Serial No. PCT / US17 / 66381, entitled “Electroactive Materials for Lithium-Ion Batteries and Other Applications”, published as International Patent Application Publication No. WO 2018 / 112182; International Patent Application Serial No. PCT / US18 / 18986, entitled “Core-Shell Electroactive Materials”, published as International Patent Application Publication No. WO No. 16 / 512,502, entitled “Electrodes for Lithium-Ion Batteries and Other Applications”.

[0126] The following examples are intended to illustrate certain embodiments of the invention, but are not intended to exemplify the full scope of the invention.

[0127] Example 1

[0128] This example provides a description of a safe electrolyte according to some embodiments of the present disclosure. This example also provides examples of making and characterizing such an electrolyte.

[0129] The electrolyte was obtained by mixing an ion dissociation compound trimethyl phosphate, a lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) and an additive in the ratio described in Table 1 by means of mechanical stirring in a liquid state at room temperature. Details of the lithium salt and the additive are listed in Table 1.

[0130] Cycling performance: The electrolyte was assembled in a 2032 button cell with lithium foil as the anode and NMC811 as the cathode (2 mAh / cm 2 ), with commercial Celgard separator as separator and carbonate-based electrolyte for comparison. Cyclic test was performed using Neware cycle tester. The charge / discharge voltage window was 2.8V to 4.5V. Figure 2 The capacity retention rate of Example 1-1 after 100 cycles at a current rate of 0.5 C is shown. The test data are listed in Table 1.

[0131] Safety: Test Protocol: This test utilizes penetration with a 3 mm stainless steel nail, with a penetration speed of approximately 80 mm / sec. The penetration is perpendicular to the plane of the cell (plane of largest surface area). The voltage and surface temperature of the cell are measured, both recorded at appropriate intervals. Figure 1 The voltage curve and thermal curve of Example 1-1 are shown.

[0132] Measurement Equipment & Calibration Data: MY44056108, Data Logger, Agilent 34970A, Last Calibration: 5 / 18 / 2018, Calibration Due: 5 / 18 / 2019.

[0133] Pre-test information and data: 1Ah pouch cell was fully charged from 2.8V to 4.5V, nail speed (80mm / sec) was programmed into the actuator.

[0134] Information and data during the test: Ambient temperature: 20.4℃, ambient humidity: 35%.

[0135] Table 1.

[0136]

[0137] Comparative Example 1 used a conventional carbonate electrolyte of 1.0 M lithium hexafluorophosphate (LiPF6) in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) (3:7 by weight). It is highly flammable.

[0138] In Examples 1-1, 1-2, and 1-3, LiTFSI, a flame-retardant trimethyl phosphate, is used as the electrolyte. Figure 1, the temperature of the sample was raised to 70.6°C without any fire or explosion, indicating that the electrolyte is highly stable for both the Li metal anode and the high voltage cathode. Therefore, the electrolyte is highly stable and safe, and can be used in systems such as high energy density Li metal batteries (LMBs). The introduction of the flame retardant trimethyl phosphate can potentially prevent fire and explosion due to excessive temperature increases in the battery, making the electrolyte non-flammable, thereby improving the safety of the battery. Low flammability electrolytes can provide enhanced safety for lithium metal and lithium ion batteries. The electrolyte can also be used in LIBs and other batteries, thereby greatly improving their safety and cyclability.

[0139] In addition, different additives were used to further improve the cycle performance. For example, in Example 1-1, 20 volume % 1,2-dimethoxyethane was introduced; in Example 1-2, 10 volume % tetraethylene glycol dimethyl ether was introduced; and in Example 1-3, 30 volume % fluoroethylene carbonate was introduced. Based on Table 1 and Figure 2 The test results in Figure 2 show that the electrolyte enables stable cycling of the Li metal anode (LMA) and greatly enhances the cycling performance of the Li / NMC811 battery (capacity retention >83% after 100 cycles at 0.5C). Without wishing to be bound by any theory, it is believed that the excellent electrochemical performance of the electrolyte is due to the LMA retaining well-concentrated Li + -FSI - -TEP is a promising candidate for the synthesis of PEGylated PEp-based poly(ethylene glycol) poly(ethylene glycol)-TEP, which is a result of the enhanced stability between the solvated structures and the improved interfacial reaction kinetics.

[0140] In addition, such electrolytes can be prepared using different Li salts at different concentrations in trimethyl phosphate. For example, the salt concentration in the electrolyte can be 0.5M to 7M.

[0141] Example 2

[0142] This example shows an electrolyte. The electrolyte is obtained by mixing the ion dissociation compound dimethyl sulfone, an additive and a lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) in the proportions described in Table 2 by mechanical stirring at room temperature in a liquid state. The electrochemical stability and cycle performance are determined. The test data are listed in Table 2.

[0143] Electrochemical stability (oxidation potential) was tested using cyclic voltammetry using an AC impedance analyzer (Interface 1010E Potentiostate, Gamry). 2The sample was sealed between a stainless steel plate and a lithium foil (reference electrode) using a commercial carbonate-based electrolyte for comparison. The charge / discharge window ranged from 2.8 to 6.0 V with a scan rate of 10 mV / s. The test was performed at room temperature. Figure 3 The electrochemical stability curves of the electrolytes of Examples 2-4 are shown.

[0144] Cycle performance: The measurement method and conditions were similar to those in Example 1. Each cell was charged and discharged for 200 cycles.

[0145] Table 2

[0146]

[0147] Compared with Comparative Example 1, in Example 2, dimethyl sulfone is introduced. Dimethyl sulfone is a highly polar aprotic solvent ion dissociation compound having high thermal stability and voltage stability window when used as an electrolyte. According to Table 2 and Figure 3 The experimental data of electrochemical stability show that the introduction of dimethyl sulfone can improve the performance of the electrolyte.

[0148] For example, on one hand, the electrolytes exhibit higher oxidation potentials (>5.0 V) than the comparative examples, indicating that the electrolytes are very stable at high voltages, making them useful in, for example, LiNi 0.5 Mn 1.5 O4 and other high-voltage lithium-ion cathode materials.

[0149] On the other hand, electrolytes exhibited <6 s g -1 The SET (self-extinguishing time) of 1.5 % was 1.3 %, indicating that the electrolyte is relatively non-flammable and improving the safety of the electrolyte. (See below for additional details on this test.)

[0150] On the other hand, the electrolyte exhibits stability to lithium metal, indicating that the electrolyte is highly stable to the Li metal anode, making the electrolyte highly stable and safe for Li metal batteries (LMBs) for high energy density. When dimethyl sulfone is used in combination with lithium bis(fluorosulfonyl)imide (LiFSI), a highly conductive lithium salt with anions having a strong fluorine-donating tendency, the electrolyte exhibits a synergistic interface formation mechanism (CEI / SEI). In summary, these interfaces enable stable coupling of the Li metal anode with the high voltage cathode over an extended temperature range.

[0151] Different additives were also used to further improve the cycling performance. In Example 2-2, 5 vol% 1,2-dimethoxyethane was introduced; in Example 2-3, 15 vol% tetraethylene glycol dimethyl ether was introduced; and in Example 2-4, 15 vol% fluoroethylene carbonate was introduced. As shown in Table 2, the additives helped to enhance the cycling performance of the Li / NMC811 battery (capacity retention rate >82% after 200 cycles at 0.5C). Without wishing to be bound by any theory, it is believed that the excellent electrochemical performance of the electrolyte is due to the LMA and the well-retained locally concentrated Li + -FSI-TEP is caused by the enhanced stability between the solvated structures and the improved interfacial reaction kinetics.

[0152] In addition, such electrolytes can be prepared using different Li salts at different concentrations in trimethyl phosphate. For example, the salt concentration in the electrolyte can be 0.5M to 7M.

[0153] Example 3

[0154] Example 3-1 to Example 3-4: Examples 3-1 to 3-4 show an electrolyte. The electrolyte is obtained by mixing a dissociation compound diethyl sulfone, a certain concentration of lithium salt (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI) (0.5 M in Examples 3-1 and 3-3, and 3 M in Examples 3-2 and 3-4), and 0.5 wt% of an additive (vinyl carbonate (VC) in Examples 3-1 and 3-2, and fluoroethylene carbonate (FEC) in Examples 3-3 and 3-4) at room temperature in a liquid state with mechanical stirring.

[0155] Embodiment 3-5 to embodiment 3-12. Embodiment 3-5 to 3-12 show polymer solid electrolytes based on sulfur-containing ion dissociation compounds. By mechanically stirring the polymer (10% in embodiments 3-5 and 3-6, 20% in embodiments 3-7 to 3-12) in a liquid state at room temperature, 1wt% AIBN as an initiator, a dissociation compound (diethyl sulfone), a certain concentration of lithium salt (bis(trifluoromethanesulfonyl)imide lithium, LiTFSI) (0.5M in embodiments 3-5, 3-7, 3-9 and 3-11; 3M in embodiments 3-6, 3-8, 3-10 and 3-12), 0.5wt% additives (vinyl carbonate (VC) in embodiments 3-9 and 3-10; fluoroethylene carbonate (FEC) in embodiments 3-11 and 3-12; and no additives in embodiments 3-5, 3-6, 3-7 and 3-8) to obtain a polymer solid electrolyte. The polymer has the structure shown below. The synthesis of the polymer is described in Example 5 of US Provisional Patent Application Serial No. 62 / 757,133 (incorporated herein by reference in its entirety).

[0156]

[0157] Comparative Examples 3-1, 3-2, and 3-3 Comparative Example 3-1 used a commercial carbonate-based electrolyte, 1 M lithium hexafluorophosphate (LiPF6) in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) (1:1 by weight).

[0158] Comparative Examples 3-2 and 3-3 are conventional carbonate-based electrolytes. The electrolyte is obtained by mixing a polymer (same as the polymer in Examples 3-5 to 3-12), 1% initiator azobisisobutyronitrile (AIBN), and 1M lithium hexafluorophosphate (LiPF6) in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) (1:1, by weight). The concentration of the polymer in Comparative Example 3-2 is 10wt%, and the concentration of the polymer in Comparative Example 3-3 is 20wt%.

[0159] The mixtures in Examples 3-5 to 3-12 and Comparative Examples 3-2 and 3-3 were each applied to a PET film. In particular, a solid electrolyte membrane was obtained by UV curing for 5 min. Electrochemical stability, electrochemical impedance spectroscopy, cycle performance, and safety performance were measured. The test data are listed in Table 3.

[0160] Electrochemical stability: The measurement method and conditions are similar to those in Example 2.

[0161] Electrochemical impedance spectroscopy. Electrochemical impedance spectroscopy was performed using an AC impedance analyzer (Interface 1010E Potentiostate, Gamry). 2 The samples were placed in 2032 button cells. The ionic conductivity was measured in the frequency range of 1 MHz to 1 Hz with a bias voltage of 10 mV. The ionic conductivity was calculated using the known thickness and area of ​​the membrane.

[0162] Cycling performance. The electrolyte was tested in an electrochemical cell using NCM811 as cathode and graphite as anode. The measurement method and conditions were similar to those of Example 1.

[0163] Self-Extinction Time (SET). Use a liquid sample. The liquid sample can be fixed in a porous support material or placed directly on a plate. Measure the time between the removal of the gas flame and the flame self-extinguishing. Report SET in seconds per gram of sample. If SET is less than 6 s g -1 If the SET is within 6s g, the sample can be determined as "non-flammable". -1 With 20s g -1If the SET is greater than 20 s g -1 , the sample can be determined as "flammable".

[0164] Table 3

[0165]

[0166] Examples 3-1 to 3-12 were tested at room temperature. Example 3-10 was also retested at 85°C. Figure 4 An example comparing the performance of Examples 3-2 and 3-10 is shown.

[0167] In Examples 3-1 to 3-13, an ion dissociation compound is introduced. The ion dissociation compound is a highly polar aprotic compound having high thermal stability and voltage stability window when used in an electrolyte. According to the experimental data shown in Table 3, the introduction of the ion dissociation compound can improve various properties of the electrolyte.

[0168] For example, on one hand, the electrolytes exhibit higher oxidation potentials (>5.0 V) than the comparative examples, indicating that the electrolytes are very stable at high voltages, making them suitable for, for example, LiNi 0.5 Mn 1.5 High voltage lithium-ion cathode materials such as O4 are useful.

[0169] On the other hand, the electrolyte exhibits a higher flash point (>170 °C) and a -1 The SET (self-extinguishing time) of 2.5 wt % NH3O2O3 was 2.3 % , indicating that the electrolyte is relatively non-flammable and improves the safety of the electrolyte.

[0170] On the other hand, the electrolyte exhibits better galvanostatic cycling performance (cycles > 300, capacity of 185 mAh / g) in an electrochemical cell at higher operating temperatures (>85°C) compared to the comparative examples. This indicates that the electrolyte is highly stable at high temperatures, making it a good candidate for high-temperature lithium batteries. The electrolyte also exhibits acceptable stability to the graphite anode, indicating that the electrolyte is highly stable and safe for Li batteries. When the ion dissociation compound is used in combination with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), a highly conductive lithium salt with anions having a strong fluorine-donating tendency, the electrolyte exhibits a synergistic interface formation mechanism (CEI / SEI). In summary, these interfaces enable stable coupling of the graphite anode and the high-voltage cathode over an extended temperature range.

[0171] Unlike Examples 3-5 to 3-13, in Examples 3-1 to 3-4, 5 wt% or 10 wt% of polymer is introduced into the liquid electrolyte to form a polymer solid electrolyte. The gel polymer electrolyte exhibits properties between liquid and solid electrolytes in terms of ionic conductivity and physical phase. From the experimental data in Table 3, if the physical integrity of the polymer solid electrolyte is promoted by using a polymer, liquid-level ionic conductivity is achieved. Problems such as electrolyte leakage and flammability can be alleviated by using a gel polymer electrolyte in an electrochemical cell.

[0172] Unlike Comparative Example 3-1, in Examples 3-11 to 3-14, vinylene carbonate (VC) or fluoroethylene carbonate (FEC) is introduced into the liquid electrolyte. Unlike Examples 3-9 to 3-13, in Examples 3-5 to 3-8, VC or FEC is introduced into the polymer solid electrolyte. The introduction of additives such as VC or FEC can improve the wetting process of battery manufacturing and testing. Some additives such as VC or FEC can preferentially decompose and undergo polymerization and ion exchange reactions at the anode / electrolyte interface to produce SEI with desired chemical composition and physical properties. For example, in Li batteries, stable SEI can comply with the cyclic volume changes at the anode during the metal atom charging (addition) and discharging (removal) of the electrode, which is conducive to stable long-term unit operation.

[0173] In a word, the introduction of flame retardant and / or sulfone seems to significantly improve various electrochemical properties. These electrolytes can help to achieve safe, long-life lithium secondary batteries. The electrolyte in these experiments shows a higher oxidation potential compared with the comparative material, indicating that they can be applied to high-voltage cathode materials. The increased oxidation potential of the electrolyte can also provide enhanced stability in both liquid electrolytes and solid electrolytes, which can provide longer life and / or higher voltage lithium batteries. In addition, the electrolyte in these embodiments shows a higher flash point and is highly stable at higher temperatures, indicating that they can be used for high-temperature lithium batteries and other purposes. These properties also can be conducive to the charge / discharge rate performance of lithium ion batteries.

[0174] Example 4

[0175] The experiments described in this example used the procedures from Examples 1 and 2 except for the modifications described below.

[0176] Examples 4-1 to 4-4 provide test information on salt concentration. As the amount of LiTFSI in dimethyl sulfone increases, the assembled Li metal button cells show better cycle stability, with the capacity retention rate increasing from 60% to 65% at 200 cycles.

[0177] Examples 4-5 to 4-10 provide the effectiveness of additives including ethylene glycol and carbonate-based derivatives.

[0178] Examples 4-2 and 4-11 show that LiTFSI is a better salt than LiPF6.

[0179] Examples 4-12 and 4-13 provide alternative sulfone derivatives as ion dissociation compounds for Li metal batteries.

[0180] The results are provided in Table 4. It was found that the commercial electrolytes had low electrochemical stability and low cycle stability for Li metal anodes. In contrast, dimethyl sulfone-based electrolytes provided higher oxidation potentials and better cycle performance in Li metal cells compared to commercial electrolytes. In addition, the addition of ethylene glycol provided better cycle performance due to the decomposition of ethylene glycol and the formation of SEI (solid electrolyte interface). In some cases, the addition of fluoroethylene carbonate can provide better cycle performance due to the decomposition of fluoroethylene carbonate and the formation of SEI. In addition, the addition of trimethyl phosphate (flame retardant) improves the safety of the battery.

[0181] The polymer used in Examples 4-14 is as follows. It also includes 40-60% dimethyl sulfone and 30-50% triethyl phosphate.

[0182]

[0183] Table 4

[0184]

[0185] Although several embodiments of the present invention have been described and illustrated herein, a person of ordinary skill in the art will readily recognize various other means and / or structures for implementing the functions described herein, and / or obtaining the results and / or one or more advantages described herein, and each such change and / or modification is considered to be within the scope of the present invention. More generally, it will be readily understood by those skilled in the art that all parameters, dimensions, materials, and configurations described herein are intended to be exemplary, and that actual parameters, dimensions, materials, and / or configurations will depend on the specific use or use of the teachings of the present invention. A person skilled in the art will recognize or be able to determine many equivalents of the specific embodiments of the present invention described herein using experiments that do not exceed routine. Therefore, it should be understood that the aforementioned embodiments are presented only by way of example, and that, within the scope of the appended claims and their equivalents, the present invention may be implemented in a manner different from that specifically described and claimed. The present invention relates to each individual feature, system, article, material, kit, and / or method described herein. In addition, if such features, systems, articles, materials, kits, and / or methods do not contradict each other, any combination of two or more such features, systems, articles, materials, kits, and / or methods is included within the scope of the present invention.

[0186] In the event that the present specification and the documents incorporated by reference include conflicting and / or inconsistent disclosures, the present specification shall control. If two or more documents incorporated by reference include mutually conflicting and / or inconsistent disclosures, the document with the later effective date shall control.

[0187] All definitions, as defined and used herein, should be understood to encompass dictionary definitions, definitions in documents incorporated by reference, and / or ordinary meanings of the defined terms.

[0188] Unless expressly indicated to the contrary, the indefinite articles "a" and "an" as used in this specification and the claims should be understood to mean "at least one".

[0189] The phrase "and / or" as used in this specification and claims should be understood to mean "either or both" of the elements so combined, i.e., elements that are present in combination in some cases and separately in other cases. Multiple elements listed with "and / or", i.e., "more than one" element so combined, should be interpreted in the same manner. In addition to the elements specifically identified by the "and / or" clause, other elements may optionally be present, whether or not related to those specifically identified. Thus, as a non-limiting example, when used in conjunction with open language such as "comprising", a reference to "A and / or B" may refer to only A (optionally including elements other than B) in one embodiment; to only B (optionally including elements other than A) in another embodiment; to both A and B (optionally including other elements) in yet another embodiment; etc.

[0190] As used in this specification and claims, "or" should be understood to have the same meaning as "and / or" as defined above. For example, when separating the items in a list, "or" or "and / or" should be interpreted as inclusive, i.e., including multiple elements or a list of elements and optionally at least one of other unlisted items, and including more than one. Only terms that clearly indicate the opposite, such as "only one (only one of)" or "exactly one (exactly one of)", or, when used in the claims, "consisting of ... " will refer to including exactly one element in a list of multiple elements or elements. Generally, the term "or" used in this article, when before exclusive terms such as "either (either)", "one of (one of)", "only one (only one of)" or "exactly one (exactly one of)", should only be interpreted as representing exclusive alternatives (i.e., "one or another but not two") .

[0191] As used in the present specification and claims, with respect to a list of more than one elements, the phrase "at least one" should be understood to mean at least one element selected from any one or more of the elements in the list of elements, but does not necessarily include at least one of each and every element specifically listed in the list of elements, and does not exclude any combination of elements in the list of elements. This definition also allows that in addition to the elements specifically identified in the list of elements to which the phrase "at least one" refers, elements may optionally be present, whether or not related to those specifically identified. Thus, as a non-limiting example, "at least one of A and B" (or equivalently, "at least one of A or B", or equivalently "at least one of A and / or B"), in one embodiment, may refer to at least one A, optionally including more than one A without B (and optionally including elements other than B); in another embodiment, may refer to at least one B, optionally including more than one B without A (and optionally including elements other than A); in yet another embodiment, may refer to at least one A, optionally including more than one A, and at least one B, optionally including more than one B (and optionally including other elements), etc.

[0192] When the word "about" is used herein with respect to a number, it should be understood that another embodiment of the present invention includes the number not modified by the presence of the word "about".

[0193] It should also be understood that in any method claimed herein that includes more than one step or action, the order of the steps or actions of the method is not necessarily limited to the order in which the steps or actions of the method are described unless explicitly stated to the contrary.

[0194] In the claims and the foregoing specification, all transitional phrases, such as "comprising," "including," "carrying," "having," "containing," "involving," "holding," and "composed of," etc., shall be construed as open-ended, i.e., including, but not limited to. Only the transitional phrases "consisting of" and "consisting essentially of" shall be closed or semi-closed transitional phrases, respectively, as set forth in Section 2111.03 of the United States Patent Office Manual of Patent Examining Procedures.

Claims

1. An electrolyte comprising: Lithium salts; Using flame retardants or sulfones as ion dissociated compounds; and Additives that can improve electrochemical cycle characteristics, The structural formula of the sulfone is R 2 -SO2-R 1 , where R 1 and R 2 may be the same or different and may be independently selected from unsubstituted alkyl, alkenyl, or alkynyl, The electrolyte further comprises a polymer, The polymer is prepared by cross-linking a mixture containing one or more polymerizable or cross-linking monomers, wherein the monomers are selected from wherein R1 comprises a structure selected from the group consisting of: wherein n is an integer between 1 and 10,000; wherein m is an integer between 1 and 5,000; wherein R2, R3, R4, R5 and R6 are each independently selected from hydrogen, methyl, ethyl, phenyl, para-methylphenyl; and where * indicates a connection point. 2 . The electrolyte according to claim 1 , wherein a volume ratio of the additive to the ion dissociation compound is not less than 5 / 95 and not more than 45 / 55.

3. The electrolyte according to any one of claims 1 or 2, wherein the additive is selected from 1,2-dimethoxyethane carbonate, fluoroethylene carbonate, vinylene carbonate, tetraethylene glycol dimethyl ether, trimethyl phosphate, and / or triethyl phosphate.

4. The electrolyte of claim 1, wherein the sulfone comprises dimethyl sulfone, diethyl sulfone, ethyl methyl sulfone, divinyl sulfone, allyl methyl sulfone, butadiene sulfone, ethyl vinyl sulfone, tetramethylene sulfone, diphenyl sulfone, methyl phenyl sulfone, isopropyl sulfone, and / or trimethylene sulfone. 5 . The electrolyte according to claim 1 , wherein the flame retardant comprises phosphorus, nitrogen, silicon and / or fluorine elements. 6 . The electrolyte according to claim 5 , wherein the flame retardant comprises methyl difluoroacetate, ethyl difluoroacetate, triethyl phosphate and / or trimethyl phosphate.

7. The electrolyte of claim 1, wherein the flame retardant has a boiling point of at least 110°C.

8. The electrolyte of claim 1, wherein the lithium salt comprises LiTFSI, LiFSI, LiBOB, LiPF6, LiBF4, LiClO4, LiAsF6, LiN(CF3SO2)2, LiC(CF3SO2)3, LiDFOB, LiF, LiCl, LiBr, LiI, Li2SO4, LiNO3, Li3PO4, Li2CO3, LiOH, lithium acetate, lithium trifluoromethyl acetate, lithium difluorophosphate, lithium 2-trifluoromethyl-4,5-dicyanoimidazole and / or lithium oxalate.

9. The electrolyte of claim 1, wherein the concentration of the lithium salt is between 1 M and 7 M.

10. The electrolyte of claim 1 or 2, wherein the concentration of the polymer in the electrolyte is between 5 wt% and 40 wt%.

11. The electrolyte of claim 1, wherein the polymer comprises a copolymer.

12. The electrolyte according to claim 11, wherein the copolymer comprises a random copolymer and / or a block copolymer.

13. The electrolyte according to claim 1, comprising a plasticizer.

14. The electrolyte according to claim 13, wherein the plasticizer comprises a polymer plasticizer, an oligoether, a nitrile, a cyclic carbonate, a small molecule plasticizer, and / or an ionic liquid.

15. The electrolyte of claim 14, wherein the polymer plasticizer comprises polyethylene oxide, polycarbonate, polyacrylonitrile and / or polylactic acid.

16. The electrolyte of claim 14, wherein the oligoether is triethylene glycol dimethyl ether.

17. The electrolyte of claim 14, wherein the nitrile comprises succinonitrile, glutaronitrile, adiponitrile and / or malononitrile. 18 . The electrolyte according to claim 14 , wherein the cyclic carbonate comprises ethylene carbonate, propylene carbonate and / or fluoroethylene carbonate.

19. The electrolyte of claim 14, wherein the small molecule plasticizer has a molecular weight of less than 1000 Daltons.

20. A polymer solid electrolyte comprising: Lithium salts; Using flame retardants or sulfones as ion dissociated compounds; Additives that can improve electrochemical cycling characteristics; and A polymer, wherein the polymer is prepared by crosslinking a mixture containing one or more polymerizable or crosslinking monomers, wherein the monomers are selected from Wherein R1 is selected from: wherein n is an integer between 1 and 10,000; wherein m is an integer between 1 and 5,000; wherein R2, R3, R4, R5 and R6 are each independently selected from hydrogen, methyl, ethyl, phenyl, para-methylphenyl; and where * indicates a connection point, The structural formula of the sulfone is R 2 -SO2-R 1 , where R 1 and R 2 may be the same or different and may be independently selected from unsubstituted alkyl, alkenyl, or alkynyl, The flash point of the electrolyte is at least 170°C.

21. The polymer solid electrolyte according to claim 20, wherein the concentration of the polymer in the polymer solid electrolyte is between 5 wt% and 40 wt%. 22 . The polymer solid electrolyte according to claim 20 , wherein a volume ratio of the additive to the ion dissociation compound is not less than 5 / 95 and not more than 45 / 55.

23. The polymer solid electrolyte of claim 20, wherein the concentration of the lithium salt is between 1 M and 7 M.

24. The polymer solid electrolyte according to claim 20, wherein the additive is selected from 1,2-dimethoxyethane carbonate, fluoroethylene carbonate, vinylene carbonate, tetraethylene glycol dimethyl ether, trimethyl phosphate, and / or triethyl phosphate.

25. The polymer solid electrolyte of claim 20, wherein the sulfone is selected from dimethyl sulfone, diethyl sulfone, ethyl methyl sulfone, divinyl sulfone, allyl methyl sulfone, butadiene sulfone, ethyl vinyl sulfone, tetramethylene sulfone, diphenyl sulfone, methyl phenyl sulfone, isopropyl sulfone, and / or trimethylene sulfone.

26. The polymer solid electrolyte according to claim 20, wherein the flame retardant is selected from methyl difluoroacetate, ethyl difluoroacetate, triethyl phosphate and / or trimethyl phosphate.

27. The polymer solid electrolyte according to claim 20, wherein the maximum operating temperature of the electrolyte is not less than 85°C.

28. An electrochemical device, characterized in that: It comprises the electrolyte according to any one of claims 1-20.

29. The electrochemical device according to claim 28, wherein the maximum operating temperature of the electrolyte is not less than 85°C.

30. The electrochemical device of claim 28, wherein the electrolyte has a self-extinguishing time of no more than 6 seconds per gram of sample.

31. The electrochemical device according to claim 28, wherein the capacity retention rate of the electrochemical device after 200 cycles at a current rate of 0.5C is not less than 72%.

32. The electrochemical device of claim 28, wherein the electrochemical device is a battery.

33. The electrochemical device of claim 28, wherein the electrochemical device is a lithium ion battery.

34. The electrochemical device of claim 28, wherein the electrochemical device is a lithium-ion solid-state battery.

35. The electrochemical device of claim 28, wherein the electrochemical device comprises an anode and a cathode.

36. The electrochemical device of claim 35, wherein the cathode comprises one or more electroactive materials.

37. The electrochemical device of claim 36, wherein the electroactive material is lithium metal, a lithium salt compound, or a combination thereof.

38. The electrochemical device of claim 36, wherein the electroactive material is selected from lithium metal oxides, S and / or FeS2.

39. The electrochemical device of claim 36, wherein the electroactive material is selected from lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium titanate, lithium manganese oxide, lithium cobalt oxide and lithium iron phosphate, LiMnPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3, LiVOPO4, LiVOPO4F, LiCoPO4F, LiCoSO4F, Li2VOP2O7, LiMnSiO4, LiNiO2, S and / or FeS2.

40. The electrochemical device of claim 39, wherein the lithium manganese oxide comprises spinel LiMn2O4, layered Li2MnO3, and / or layered LiMnO2.

41. The electrochemical device of claim 35, wherein the anode comprises one or more electroactive materials.

42. The electrochemical device of claim 41, wherein the electroactive material comprises lithium metal, Gr, Si, Si / Gr, Sn and / or Li4Ti5O 12 .

43. The electrochemical device of claim 35, wherein the anode comprises a conductive carbon material.

44. The electrochemical device of claim 43, wherein the conductive carbon material comprises graphite, hard carbon, porous hollow carbon spheres and / or carbon tubes.

45. The electrochemical device according to claim 28, wherein the electrolyte comprises 0.8M LiTFSI as the lithium salt, 1,2-dimethoxyethane as the additive, and trimethyl phosphate as the ion dissociation compound, wherein the volume ratio of 1,2-dimethoxyethane to trimethyl phosphate is 20 / 80.

46. ​​The electrochemical device according to claim 45, wherein the capacity retention of the electrochemical device after 100 cycles at a current rate of 0.5C is 80%.

47. The electrochemical device according to claim 28, wherein the electrolyte comprises 1.0 M LiTFSI as the lithium salt, 10 vol% tetraglyme as the additive, and trimethyl phosphate as the ion dissociation compound.

48. The electrochemical device according to claim 47, wherein the capacity retention of the electrochemical device after 100 cycles at a current rate of 0.5C is 75%.

49. The electrochemical device according to claim 28, wherein the electrolyte comprises 1.2M LiTFSI as the lithium salt, 30 vol% fluoroethylene carbonate as the additive, and trimethyl phosphate as the ion dissociation compound.

50. The electrochemical device according to claim 49, wherein the capacity retention of the electrochemical device after 100 cycles at a current rate of 0.5C is 83%.

51. The electrochemical device according to claim 28, wherein the electrolyte comprises 1.0 M LiTFSI as the lithium salt, 5 vol% 1,2-dimethoxyethane as the additive, and dimethyl sulfone as the ion dissociation compound.

52. The electrochemical device according to claim 51, wherein the oxidation potential of the electrolyte to Li / Li+ is 5.0 V and the capacity retention of the electrochemical device after 200 cycles at a current rate of 0.5 C is 72%.

53. The electrochemical device of claim 28, wherein the electrolyte comprises 1.2 M LiTFSI as the lithium salt, 15 vol% tetraglyme as the additive, and dimethyl sulfone as the ion dissociation compound.

54. The electrochemical device according to claim 53, wherein the oxidation potential of the electrolyte to Li / Li+ is 5.1 V and the capacity retention of the electrochemical device after 200 cycles at a current rate of 0.5 C is 77%.

55. The electrochemical device according to claim 28, wherein the electrolyte comprises 1.8M LiTFSI as the lithium salt, 5 vol% fluoroethylene carbonate as the additive, and dimethyl sulfone as the ion dissociation compound.

56. The electrochemical device according to claim 55, wherein the oxidation potential of the electrolyte to Li / Li+ is 5.5 V and the capacity retention of the electrochemical device after 200 cycles at a current rate of 0.5 C is 82%.

57. The electrochemical device according to claim 28, wherein the electrolyte comprises 0.5M LiTFSI as the lithium salt, 0.5wt% vinylene carbonate as the additive, and diethyl sulfone as the ion dissociation compound.

58. The electrochemical device according to claim 57, wherein the electrolyte has an oxidation potential greater than 5.0 V for Li / Li+ and an ionic conductivity of 3.2×10 -4 S / cm, the maximum operating temperature is greater than 85°C, and the electrochemical device has an initial battery capacity of 80 mAh / g at a current rate of 0.5C and can be cycled more than 300 times.

59. The electrochemical device according to claim 28, wherein the electrolyte comprises 3M LiTFSI as the lithium salt, 0.5 wt% vinylene carbonate as the additive, and diethyl sulfone as the ion dissociation compound.

60. The electrochemical device according to claim 59, wherein at room temperature, the electrolyte has an oxidation potential greater than 5.0 V for Li / Li+ and an ionic conductivity of 2.8×10 -4 S / cm, the maximum operating temperature is greater than 85°C, and the electrochemical device has an initial battery capacity of 185 mAh / g at a current rate of 0.5C and can be cycled more than 300 times.

61. The electrochemical device according to claim 28, wherein the electrolyte comprises 0.5 M LiTFSI as the lithium salt, 0.5 wt% fluoroethylene carbonate as the additive, and diethyl sulfone as the ion dissociation compound.

62. The electrochemical device of claim 61, wherein at room temperature, the oxidation potential of the electrolyte to Li / Li+ is greater than 5.0 V, the maximum operating temperature is greater than 85°C, and the electrochemical device has an initial battery capacity of 112 mAh / g at a current rate of 0.5C and can be cycled more than 300 times.

63. The electrochemical device according to claim 28, wherein the electrolyte comprises 3M LiTFSI as the lithium salt, 0.5 wt% fluoroethylene carbonate as the additive, and diethyl sulfone as the ion dissociation compound.

64. The electrochemical device according to claim 63, wherein at room temperature, the electrolyte has an oxidation potential of greater than 5.0 V for Li / Li+ and an ionic conductivity of 2.8×10 -4 S / cm, the maximum operating temperature is greater than 85°C, and the electrochemical device has an initial battery capacity of 175 mAh / g at a current rate of 0.5C and can be cycled more than 300 times.

65. The electrochemical device according to claim 28, wherein the electrolyte is prepared by cross-linking a mixture containing a polymerizable or cross-linkable monomer, the lithium salt, the additive, and the dissociative compound.

66. The electrochemical device of claim 65, wherein the polymerizable or cross-linkable monomer is selected from wherein R1 comprises a structure selected from the group consisting of: wherein n is an integer between 1 and 10,000; wherein m is an integer between 1 and 5,000; wherein R2, R3, R4, R5 and R6 are each independently selected from hydrogen, methyl, ethyl, phenyl, para-methylphenyl; and where * indicates a connection point.

67. The electrochemical device according to claim 65, wherein the mixture contains 5 wt% to 40 wt% of the polymerizable or cross-linkable monomer.

68. The electrochemical device of claim 65, wherein the mixture is cross-linked by exposure to UV light, heat, and / or an initiator.

69. The electrochemical device of claim 68, wherein the mole fraction of the initiator is between 0.001 and 0.

01.

70. The electrochemical device of claim 68, wherein the initiator comprises benzoyl peroxide, 2,2'-azobisisobutyronitrile (AIBN), 4,4-azobis(4-cyanovaleric acid) (ACVA), and / or potassium persulfate.

71. The electrochemical device according to claim 65, wherein the mixture comprises 0.5M LiTFSI as the lithium salt, 0.5wt% vinylene carbonate as the additive, diethyl sulfone as the ion dissociation compound, 1wt% AIBN as the initiator, and 20wt% of the following monomers as the polymerizable or cross-linkable monomers 72. The electrochemical device according to claim 71, wherein at room temperature, the electrolyte has an oxidation potential greater than 4.5 V for Li / Li+ and an ionic conductivity of 0.8×10 -4 S / cm, the maximum operating temperature is greater than 85°C, and the electrochemical device can be cycled more than 200 times.

73. The electrochemical device according to claim 65, wherein the electrolyte comprises 3M LiTFSI as the lithium salt, 0.5wt% vinylene carbonate as the additive, diethyl sulfone as the ion dissociation compound, 1wt% AIBN, and 20wt% of the following monomers as the polymerizable or cross-linkable monomers 74. The electrochemical device according to claim 73, wherein at room temperature, the electrolyte has an oxidation potential greater than 4.5 V for Li / Li+ and an ionic conductivity of 0.7×10 -4 S / cm, the maximum operating temperature is greater than 85°C, and the electrochemical device has an initial battery capacity of 162 mAh / g at a current rate of 0.5C and can be cycled more than 200 times.

75. The electrochemical device according to claim 73, wherein at 85°C, the electrolyte has an oxidation potential of greater than 4.5 V for Li / Li+ and an ionic conductivity of 1.1×10 -4 S / cm, and the initial battery capacity of the electrochemical device is 169 mAh / g at a current rate of 0.5 C and can be cycled for more than 200 times.

76. The electrochemical device according to claim 65, wherein the electrolyte comprises 0.5M LiTFSI as the lithium salt, 0.5wt% fluoroethylene carbonate as the additive, diethyl sulfone as the ion dissociation compound, 1wt% AIBN, and 20wt% of the following monomers as the polymerizable or cross-linkable monomers 77. The electrochemical device according to claim 76, wherein at room temperature, the electrolyte has an oxidation potential of greater than 4.5 V for Li / Li+ and an ionic conductivity of 0.8×10 -4 S / cm, the maximum operating temperature is greater than 85°C, and the electrochemical device can be cycled more than 200 times.

78. The electrochemical device according to claim 65, wherein the electrolyte comprises 3M LiTFSI as the lithium salt, 0.5wt% fluoroethylene carbonate as the additive, diethyl sulfone as the ion dissociation compound, 1wt% AIBN, and 20wt% of the following monomers as the polymerizable or cross-linkable monomers 79. The electrochemical device according to claim 78, wherein at room temperature, the electrolyte has an oxidation potential of greater than 4.5 V for Li / Li+ and an ionic conductivity of 0.7×10 -4 S / cm, the maximum operating temperature is greater than 85°C, and the electrochemical device has an initial battery capacity of 152 mAh / g at a current rate of 0.5C and can be cycled more than 200 times.

80. The electrochemical device according to claim 28, wherein the electrolyte comprises 1.8M LiTFSI as the lithium salt, 1,2-dimethoxyethane as the additive, and dimethyl sulfone as the ion dissociation compound, wherein the volume ratio of 1,2-dimethoxyethane to dimethyl sulfone is 5 / 95.

81. The electrochemical device according to claim 80, wherein the oxidation potential of the electrolyte to Li / Li+ is 5.1 V, and the capacity retention rate of the electrochemical device after 200 cycles at a current rate of 0.5 C is 74%.

82. The electrochemical device according to claim 28, wherein the electrolyte comprises 1.8 M LiTFSI as the lithium salt, tetraglyme and dimethyl sulfone as the ion dissociation compounds, wherein the volume ratio of tetraglyme to dimethyl sulfone is 15 / 85.

83. The electrochemical device according to claim 82, wherein the oxidation potential of the electrolyte to Li / Li+ is 5.2 V, and the capacity retention rate of the electrochemical device after 200 cycles at a current rate of 0.5 C is 81%.

84. The electrochemical device according to claim 28, wherein the electrolyte comprises 1.8M LiTFSI as the lithium salt, fluoroethylene carbonate as the additive, and dimethyl sulfone as the ion dissociation compound, wherein the volume ratio of fluoroethylene carbonate to dimethyl sulfone is 8 / 92.

85. The electrochemical device according to claim 84, wherein the oxidation potential of the electrolyte to Li / Li+ is 5.5 V, and the capacity retention rate of the electrochemical device after 200 cycles at a current rate of 0.5 C is 85%.

86. The electrochemical device according to claim 28, wherein the electrolyte comprises 1.8M LiTFSI as the lithium salt, trimethyl phosphate as the additive, and dimethyl sulfone as the ion dissociation compound, wherein the volume ratio of trimethyl phosphate to dimethyl sulfone is 40 / 60.

87. The electrochemical device according to claim 86, wherein the oxidation potential of the electrolyte to Li / Li+ is 5.3 V, and the capacity retention rate of the electrochemical device after 200 cycles at a current rate of 0.5 C is 82%.

88. The electrochemical device according to claim 28, wherein the electrolyte comprises 1.8M LiTFSI as the lithium salt, triethyl phosphate as the additive, and dimethyl sulfone as the ion dissociation compound, wherein the volume ratio of triethyl phosphate to dimethyl sulfone is 40 / 60.

89. The electrochemical device according to claim 88, wherein the oxidation potential of the electrolyte to Li / Li+ is 5.2 V, and the capacity retention rate of the electrochemical device after 200 cycles at a current rate of 0.5 C is 80%.

90. The electrochemical device according to claim 28, wherein the electrolyte comprises 1.8 M LiTFSI as the lithium salt, trimethyl phosphate and fluoroethylene carbonate as the additives, and dimethyl sulfone as the ion dissociation compound, wherein the volume ratio of trimethyl phosphate, fluoroethylene carbonate, and dimethyl sulfone is 40 / 5 / 55.

91. The electrochemical device according to claim 90, wherein the oxidation potential of the electrolyte to Li / Li+ is 5.3 V, and the capacity retention rate of the electrochemical device after 200 cycles at a current rate of 0.5 C is 85%.

92. The electrochemical device according to claim 28, wherein the electrolyte is a polymer solid electrolyte prepared by cross-linking a mixture containing the following monomers: The mixture contains 1.8M LiTFSI as the lithium salt, trimethyl phosphate and fluoroethylene carbonate as the additives, and dimethyl sulfone as the dissociated compound, wherein the volume ratio of trimethyl phosphate, fluoroethylene carbonate and dimethyl sulfone is 40 / 5 / 55; and the weight fraction of the monomer in the mixture is 10%.

93. The electrochemical device according to claim 72, wherein the oxidation potential of the electrolyte to Li / Li+ is 5.0 V, and the capacity retention rate of the electrochemical device is 80% after 200 cycles at a current rate of 0.5C.

Citation Information

Patent Citations

  • Ionomer electrode manufacturing slurry

    US20190020033A1

  • Poly(lithium acrylate) and other materials for membranes and other applications

    US20190051939A1

  • Polymer solid electrolytes

    US20200144665A1

  • Electrodes for lithium-ion batteries and other applications

    US20210020944A1

  • Car-coupling

    US512495A